A LOW-COST WEB-BASED ADMINISTRATION SYSTEM FOR SOLAR-INTEGRATED PALM SUGAR PRODUCTION - Offel Arianti Rumagit; Melky Krisna Elia Paendong; Arief Perdana Kumaat; Misael Aldo Walangitan; Gratia Natrina Kaparang; Putri Harunja (CV. TOTUS TUUS, 2026)
Rural palm sugar producers increasingly combine traditional processing with photovoltaic systems, but production, quality, cost, and solar-use records often remain fragmented. This study designed and field-demonstrated a low-cost web-based administration system for Kelompok Tani Talaut Jaya in North Sulawesi, Indonesia. Following design science research, the study analyzed the group's paper forms, developed a Google Sheets and Google Apps Script prototype, demonstrated the artifact across several production cycles, and revised it through field observation and informal user feedback. The group leader and several producers used the system through four functional roles: operator, quality control, leadership, and administrator. The artifact integrates five modules: raw-material receiving, daily production, output quality, production-cost calculation, and solar-energy-use logging. Functional verification covered role-based access, transaction recording, automated calculation of Harga Pokok Produksi (HPP), and monthly PDF report generation. The evaluation was descriptive; exact user numbers, transaction volumes, task-completion times, error rates, and standardized acceptance scores were not formally recorded. The verified final forms contain six, six, six, five, and six data-entry fields, respectively. Only the production-cost module retained a documented initial count of ten fields, so the study does not claim a measured reduction across all modules. The solar-energy module documents utilization conditions but does not quantify energy savings or causal production effects. The findings support feasibility in one partner setting and require multi-site validation using formal usability, accuracy, time, and metered-energy measures.